"This is the worst that has happened to me in 86 years": A qualitative study of the experiences of grandparents losing a grandchild due to a neurological or oncological disease. Issue 1 (28th September 2020) - Flury, Maria; Orellana‐Rios, Claudia L.; Bergsträsser, Eva; Becker, Gerhild
Abstract: Purpose: Pediatric palliative care focuses mainly on the children suffering from a life‐limiting disease, but always includes parents and siblings. However, grandparents are also often highly involved in caring for the child and require additional attention. Therefore, the aim of this study was to investigate the experiences of grandparents during the end‐of‐life care and after the death of a grandchild. Design and Methods: A qualitative approach using semi‐structured interviews was chosen. Fifteen grandparents of 10 children who had died of neurological or oncological diseases were interviewed. Participants were recruited among the families cared by the pediatric palliative care team of a children's hospital in northern Switzerland. Grandparents were interviewed at least 1 year after the death of the grandchild. The data was analyzed employing reconstructive interview analysis. Results: Regardless of the child's diagnosis and circumstances of death, the participants described how the child's death had a major impact on them and their entire family. Grandparents felt obligated to support the family and constantly be a source of support for the parents. They bore a heavy psychological burden as they cared and mourned not only for their dying grandchild but also for their own daughter or son. Grandparents struggled with their ability to communicate about disease and death. They tried to process and make sense of their loss by remembering the deceased child. Practice Implications: These findings emphasize the importance of identifying and understanding grandparents' suffering. Pediatric palliative care teams can achieve this by actively making contact with grandparents, taking their concerns seriously and demonstrating appreciation for their role in supporting the family.